Effects of butafosfan with or without cyanocobalamin on the metabolism of early lactating cows with subclinical ketosis. Issue 1 (28th April 2015) - Nuber, U.; van Dorland, H. A.; Bruckmaier, R. M.
Summary: Fifty‐one dairy cows with subclinical ketosis were used to investigate the effects of butafosfan alone or in combination with cyanocobalamin on metabolism. Treatments included i.v. injection of 10 ml/100 kg of body weight with butafosfan (BUT) or combined cyanocobalamin with butafosfan (BUTCO) at a similar concentration as in Catosal ® . Control cows (CON) received a 0.9% saline solution. Cows were injected on days 1–3 at 22.3 ± 0.7 days post‐partum. Milk production and composition were not affected by the treatments. In plasma, CON cows had a significantly higher plasma NEFA concentration (0.59 ± 0.03 mm ) across the study period than BUTCO cows (p   <   0.05; 0.42 ± 0.03 mm ), whereas the plasma NEFA concentration of BUT was intermediate (0.52 ± 0.03 mm ) but not significantly different from CON. Both BUTCO and BUT cows had lower (p   <   0.05) plasma BHBA concentrations (1.02 ± 0.06 mm and 1.21 ± 0.06 mm, respectively) across the study period than CON (1.34 ± 0.06 mm ). Plasma glucose was not different between treatments, but plasma glucagon concentrations were consistently high in BUT compared to BUTCO and CON. Lowest post‐treatment glucagon levels were observed in BUTCO. Hepatic mRNA abundance of liver X receptor α, a nuclear receptor protein involved in lipid metabolism, was higher in BUTCO compared to BUT and CON (p   <   0.05) on day 7. Furthermore, on day 7, the mRNA abundance of beta‐hydroxybutyrate dehydrogenase 2 was higher in BUTCO compared to BUT and CON (p   <   0.01). In conclusion, injections of combined cyanocobalamin with butafosfan post‐partum in early lactation ketotic dairy cows act on lipid metabolism with effects on plasma metabolites, most likely mediated via modified activity of key factors in the liver. Results indicate that the application of butafosfan only in combination with cyanocobalamin exhibits the expected positive effects on metabolism.